2018
DOI: 10.1055/s-0038-1671441
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia are dysfunctional in obese adipose-derived mesenchymal stem cells

Abstract: Adipose-derived mesenchymal stem cells (ASCs) have crucial functions, but their roles in obesity are not well defined. We show here that ASCs from obese individuals have defective primary cilia, which are shortened and unable to properly respond to stimuli. Impaired cilia compromise ASC functionalities. Exposure to obesity-related hypoxia and cytokines shortens cilia of lean ASCs. Like obese ASCs, lean ASCs treated with interleukin-6 are deficient in the Hedgehog pathway, and their differentiation capability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 23 publications
1
20
0
5
Order By: Relevance
“…Furthermore, it is crucial to understand why/how ASCs alter their functions in obesity. Recently, we have reported that, compared with control ASCs, obese ASCs display defective primary cilia, which are shortened and unable to properly respond to various stimuli . Impaired primary cilia compromise ASC functionalities like differentiation and motility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is crucial to understand why/how ASCs alter their functions in obesity. Recently, we have reported that, compared with control ASCs, obese ASCs display defective primary cilia, which are shortened and unable to properly respond to various stimuli . Impaired primary cilia compromise ASC functionalities like differentiation and motility .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that, compared with control ASCs, obese ASCs display defective primary cilia, which are shortened and unable to properly respond to various stimuli . Impaired primary cilia compromise ASC functionalities like differentiation and motility . Further work is warranted to investigate the biology of ASCs in normal and obese adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and real-time PCR were performed as described (Kreis et al, 2019a;Ritter et al, 2018).…”
Section: Cell Viability Wound Healing/migration Invasion Assay Andmentioning
confidence: 99%
“…Importantly, the Hh signalling pathway is deficient in obese ASCs, accompanied by reduced expression of its related genes like GLI1, PTCH1, SMO and the homeobox protein NANOG. The latter is known as a direct target of the Hh pathway in glioma stem cells and ASCs (63,64). These transcription factors are associated with the self-renewal of stem cells (65,66), and thus, altered expression of these genes may explain reduced undifferentiated multipotency of ASCs in the obese state (16,67).…”
Section: Dysfunctional Primary Cilia In Obese Adipose-derived Mesenchmentioning
confidence: 99%